The Study of the Efficacy of Bibliotherapy in Detachment Anxiety and Depression of Children of Divorced Parents - Y. Banki; Sh. Amiri; S. Asadi (روانشناسی بالینی و شخصیت, 2009)
This research studied the efficacy of bibliotherapy in detachment anxiety and depression of children of divorced parents. Through random sampling 30 children were selected from 6to8- year-old children of divorced parents in Isfahan. Then, they were assigned to the experimental and control groups. The research design was a semi-experimental one pretest and posttest were administered to the control group. Ontario's list of child health (intrinsic disorders, detachment anxiety and depression) was used. The experimental group received group bibliotherapy with a book called" Little bear, you are not guilty". It was designed to decrease tension, anxiety and sense of guilt of children of divorced parents. The data were analyzed using covariance analysis. The results indicated that the effect of group bibliotherapy on detachment anxiety and depression scores of children was significant (p=.011, p=.042, respectively). Moreover, the effect of group bibliotherapy on follow up scores of depression in children was significant (p=.002), as well.